Exploring citizen data to improve trustworthiness and quality of ONS’ population and migration statistics - Buckley, Alex; McSweeney, Rachel (International Journal of Population Data Science, 2025)
Objectives The Citizen Data team is undertaking innovative research with Civil Society Organisations (CSOS) across England and Wales, to explore how the citizen data they produce can be used to improve the trustworthiness and quality of the Office for National Statistics’ population and migration statistics in the future. Methods Through a case study approach, using a blend of exploratory qualitative methods, ONS is exploring the processes and best practices undertaken by a range of CSOs who produce data with the citizens which they serve. We will assess the features and quality of a range of citizen data sources using a framework which we have developed based on recognised statistical and analysis frameworks, and explore the approaches and best practices of a selection of CSOs in their data collection initiatives. Results Our work will explore the potential of these largely untapped resources to contribute valuable data and understanding on characteristics of under-represented groups. We expect the case studies to provide an in-depth picture of some of the opportunities to work with and use citizen data collected through trusted community-led organisations. These opportunities may help us to produce more accurate or timely outputs, or better coverage and representativeness. The research will also consider the potential benefits of the citizen data approach on the trustworthiness of ONS, and with our future of population and migration statistics programme. In conjunction with the evaluatory phase, the project will contribute to a framework for working in partnership with CSOs on citizen data initiatives in future. Conclusion Citizen data initiatives have the potential to improve the quality and trustworthiness of official statistics and analysis.. This research will provide insights into the best practice and processes of Civil Society Organisations in generating citizen data, how we can innovate the practices of a world-leading National Statistical Organisation, and provide a blueprint for the cultivation of these relationships and data production processes.